IMPACT OF WORLD BANK PROJECTS ON THE DEVELOPMENT OF THE COUNTRY’S INDUSTRY (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This study investigates the Impact of World Bank Projects on the Development of the Country’s Industry, focusing on how international financial assistance influences industrial growth and economic development in recipient countries. The World Bank, as a leading global financial institution, plays a pivotal role in shaping industrial policies through its funding mechanisms, technical assistance, and capacity-building initiatives. This research employs a mixedmethods approach, combining quantitative data analysis with qualitative case studies from various countries that have received World Bank support.